Maternal-foetal transfer of Plasmodium falciparum and Plasmodium vivax antibodies in a low transmission setting - Charnaud, S; McGready, R; Herten-Crabb, A; Powell, R; Guy, A; Langer, C; Richards, J; Gilson, P; Chotivanich, K; Tsuboi, T; Narum, D; Pimanpanarak, M; et al. (Nature Publishing, 2016)
During pregnancy immunolglobulin G (IgG) antibodies are transferred from mother to neonate across the placenta. Studies in high transmission areas have shown transfer of P. falciparum-specific IgG, but the extent and factors influencing maternal-foetal transfer in low transmission areas co-endemic for both P. falciparum and P. vivax are unknown. Pregnant women were screened weekly for Plasmodium infection. Mother-neonate paired serum samples at delivery were tested for IgG to antigens from P. falciparum, P. vivax and other infectious diseases. Antibodies to malarial and non-malarial antigens were highly correlated between maternal and neonatal samples (median [range] spearman ρ = 0.78 [0.57-0.93]), although Plasmodium spp. antibodies tended to be lower in neonates than mothers. Estimated gestational age at last P. falciparum infection, but not P. vivax infection, was positively associated with antibody levels in the neonate (P. falciparum merozoite, spearman ρ median [range] 0.42 [0.33-0.66], PfVAR2CSA 0.69; P. vivax ρ = 0.19 [0.09-0.3]). Maternal-foetal transfer of anti-malarial IgG to Plasmodium spp. antigens occurs in low transmission settings. P. vivax IgG acquisition is not associated with recent exposure unlike P. falciparum IgG, suggesting a difference in acquisition of antibodies. IgG transfer is greatest in the final weeks of pregnancy which has implications for the timing of future malaria vaccination strategies in pregnant women.